Le langage de la diversité - Sara Ahmed (Glad!)
This article asks the question, “what does diversity do?” by drawing on interviews with diversity practitioners based in higher education in the United Kingdom and Australia. Feminist and postcolonial scholars have offered powerful critiques of the language of diversity. This essay aims to contribute to the debate by examining how diversity workers work with the term diversity within the context of education. It shows that diversity as a term is used strategically by practitioners as a solution to what has been called “equity fatigue”; it is a term that more easily supports existing organizational ideals or even organizational pride. What makes diversity useful also makes it limited: it can become detached from histories of struggle for equality. The article explores how practitioners have to re-attach the word diversity to other words (such as equality and justice), which evoke such histories. Diversity workers aim to get organizations to commit to diversity. However, what that commitment means still depends on how diversity circulates as a term within organizations.